Ironies of colonial governance : law, custom and justice in colonial India - Jaffe, James (Cambridge studies in law and society, 2015)
"This book concerns several discussions, discussions that took place first among British officers and officials serving in India or residing in London and then among Indian nationalists. The discussions concerned the nature and function of the Indian village council - the panchayat - its place in Indian society, and its role in the British governance of India. Much like the Peter Robb's work on the Bengal Tenancy Act, I have tried to "treat the evolution of events and concepts as the outcome of a dialogue between various, changing, mutually-influenced voices." More specifically, it is about the colonial imagination of indigenous legal customs and government and the attempts to adapt those imagined customs to the practices of colonial governance. It thus adopts a transnational perspective that emphasizes the ideological sources of Western perceptions of indigenous governing practices, the variety of efforts to "revive" and implement these "authentic" institutions, and the unintended consequences that resulted. Therefore, it recounts the complicated and contested history of the construction of colonial knowledge and the political and intellectual influences that shaped it"--